A most wanted man [videorecording (DVD)] - Dafoe, Willem; Hoffman, Philip Seymour, 1967-2014; McAdams, Rachel, 1978-; Le Carré, John, 1931- (Lions Gate Entertainment, 2014)
German intelligence agent Gunther Bachmann (Philip Seymour Hoffman, in his final starring role) must race against time to solve a perilous mystery: Is the half-Chechen, half-Russian Muslim who's surfaced in Hamburg a victim seeking refuge, or a terrorist seeking revenge?